Skizofrenia Paranoid pada Guru Sekolah Dasar Perempuan Berusia 29 Tahun: Suatu Laporan Kasus - Alfiansya Noval Siswanto; Era Catur Prasetya (Galen: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Background: Schizophrenia, particularly the paranoid subtype, contributes significantly to global neuropsychiatric disability, with rising prevalence from 13.6 million cases (1990) to 23.1 million (2021). This case addresses management challenges in high-functioning young adults. Objective: To document clinical characteristics, biopsychosocial management, and relapse factors in paranoid schizophrenia. Methods: Qualitative descriptive single case study at Psychiatry Polyclinic, Muhammadiyah Lamongan Hospital. Population and Sample: Outpatients with F20.0 diagnosis; purposive sampling of one 29-year-old female elementary teacher (GAF 61-70). Instruments and Analysis: PPDGJ-III, DSM-5, multi-axial assessment; thematic content analysis with data triangulation. Results: Patient exhibited 10-year history of auditory hallucinations, sleep disturbance, anxiety, and social withdrawal, responsive to Clozapine-Risperidone combination, CBT, and family psychoeducation, improving social function despite relapses. Conclusion: Integrated biopsychosocial approach enables professional functioning; single-case design limits generalizability, recommending multi-case cohorts with neuroimaging.